2017
DOI: 10.1021/acs.langmuir.7b01021
|View full text |Cite
|
Sign up to set email alerts
|

Combining Precipitation and Vitrification to Control the Number of Surface Patches on Polymer Nanocolloids

Abstract: In an effort to incorporate increasingly higher levels of functionality into soft nanoparticles, heterogeneously structured particles stand out as a simple means to enhance functionality by tailoring only particle architecture. Various means exist for the fabrication of particles with specific structural configurations; however, the tunability of particle morphology is still a challenging and often laborious task, especially in self-assembled systems where a single equilibrium configuration dominates. Improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…ν is the Flory exponent, which depends on solvent conditions. For the polystyrene chains with a molecular weight of 16.5 kg/mol studied in the experiments, 11,22,23 our coarse-graining method leads to N b = 23. 11 In addition, the values of ν for different solvent conditions have been calculated from MD simulations and are presented in Fig.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ν is the Flory exponent, which depends on solvent conditions. For the polystyrene chains with a molecular weight of 16.5 kg/mol studied in the experiments, 11,22,23 our coarse-graining method leads to N b = 23. 11 In addition, the values of ν for different solvent conditions have been calculated from MD simulations and are presented in Fig.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…Compared to other competing methods, e.g., templating, 12,13 particle lithography, 14,15 or Self-Organized Precipitation (SORP), [16][17][18][19] FNP stands out as a one-step continuous process that operates at room temperature, consumes little energy, and has potential to scale up. In addition, it has also been demonstrated both by experiments and by simulations that it is able to access a wide range of structures, including Janus, core-shell, 20,21 patchy, [22][23][24] and concentric lamellar, 25 using different feed materials, with reliable control over particle size, morphology, and composition. This process can make use of electroneutral polymers with no external stabilizing agents.…”
Section: Introductionmentioning
confidence: 99%
“…Sosa et al co-precipitated glassy polymer (PS) and nonglassy polymer (PI) at temperature below the glass transition temperature (T g ) of PS, below which the vitrified PS polymer inhibits the structural change and the two polymers phase-separate into a nonequilibrium structure of heteroaggregate, as shown in Figure 2e. [33] If the particles are annealed at 135°C, which is higher than the T g of PS, PS aggregates start to form a single domain, forming spherical Janus particles. This is because vitrified PS aggregates are able to anneal above T g to reach the thermal equilibrium state.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…When mixing polymers with different glass transition temperature, vitrification of polymer blends strongly determines the particle structures ( Figure 5B,C). [37,38] Furthermore, they also found that diblock copolymers with a different molecular weight could form various internal nanostructures ranging from an ordered concentric lamella to a disordered lamellar morphology. The increase of molecular weight led to a disorder in lamella orientation which further caused complex internally structured colloids.…”
Section: Flash Nanoprecipitationmentioning
confidence: 99%
“…Reproduced with permission. [37] Copyright 2017, American Chemical Society morphologies were generated when using blends of a BCP and a homopolymer. Additional phase separation and chain kinetic trapping effects lead to complicated situations for the polymer blends.…”
Section: Flash Nanoprecipitationmentioning
confidence: 99%